1945
DOI: 10.1192/bjp.91.384.318
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Responses in Prefrontal Leucotomy

Abstract: In bilateral prefrontal leucotomy inter alia the fronto-subthalamic, the fronto septal and fronto-hypothalamic (posterior) projections may be severed, together with reciprocally projecting tracts. These may represent the anatomical basis for the altered autonomic visceral disturbances observed following operations. The reports on bilateral leucotomy emphasize the post-operative “improvement in autonomic functions with a tendency to gain weight” (Vonderahe). After lobotomy transient visceral disturbances make t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1947
1947
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…Carscallen, Buck, and Hobbs (1951) have shown that after leucotomy schizophrenics show impiroved temperature regulation. These findings also are in line with Reitman's (1945) conclusions that with schizophrenic patients after standard leucotomy there is a tendency towards increased rather than decreased " homeostasis ". We would add that leucotomy also reduces the abnormal autonomic activity associated with the mental disease.…”
Section: Change In Palmar Sweating After Leucotomysupporting
confidence: 91%
“…Carscallen, Buck, and Hobbs (1951) have shown that after leucotomy schizophrenics show impiroved temperature regulation. These findings also are in line with Reitman's (1945) conclusions that with schizophrenic patients after standard leucotomy there is a tendency towards increased rather than decreased " homeostasis ". We would add that leucotomy also reduces the abnormal autonomic activity associated with the mental disease.…”
Section: Change In Palmar Sweating After Leucotomysupporting
confidence: 91%
“…Lobotomy has been shown to result hi widespread changes in the autonomic balance (10), and it undoubtedly induces further changes in the nervous system and perhaps indirectly in other bodily systems. If such is the case, it becomes difficult, if not impossible, to determine whether a behavioral change following lobotomy is a direct result of brain damage or an indirect result of induced changes in other parts of the organism following lobotomy.…”
Section: Discussionmentioning
confidence: 99%
“…In this case the lesion was thought to be central. Reitman (1945) and many other workers have demonstrated changes in autonomic functions following bilateral prefrontal leucotomy. Taking advantage of this operation Livingston and his co-workers (Livingston, Chapman, Livingston, and Kraintz, 1948) have shown that electrical stimulation of the orbital surface of the frontal lobes may cause marked changes in the blood pressure and in respiration.…”
mentioning
confidence: 91%
“…At that time she suggested that the frontal poles were autonomic centres distinct from the motor cortex but was able to adduce little evidence as to their exact role. Since Kennard's review Reitman (1945) and several subsequent authors have reported transient changes in autonomic regulatory functions following prefrontal leucotomy. Apart from the observations of Fairman and his co-workers (Fairman, Livingston, and Poppen, 1950), we are not aware of any previous studies to investigate whether unilateral autonomic changes can be demonstrated following unilateral leucotomy.…”
mentioning
confidence: 99%